A FIGURA FEMININA NA SOCIEDADE - De Carli, Eliane Maria; GRAZZIOLA, Ana Carolina; Silva, Leticia Helen (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2019)
This work has the role of women in the face of society. What is a research project that aims to disseminate quantitative, qualitative information and even curiosities about how a woman fits into a society? society imposes. To do this, inspect in books and online, as well as a file created by people as a basis, information that may be present in discussions and discussions. As a result, there is a need for a broader view of the concept of women, understanding that she is not only an individual, but can be presented in a collective way that must be respected and treated with equality.